ANKLE BRACHIAL INDEX DAN SENSITIFITAS KAKI PADA PASIEN DM TIPE II - Galvani Volta Simanjuntak; Janno Sinaga; Marthalena Simamora (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Ankle brachial Index (ABI) is an examination to determine of vascularization in the lower leg in T2DM patients. Vascular disorders in the lower legcan predicted nerve function problem in the legs (peripheral diabetic neuropathy). The purpose study was to exploration the ankle brachial index in T2DM patiens and its correlation with foot sensory. This study was an observational analytic with cross sectional design with population was type II DM patients in diabetic clinic Sari Mutiara Hospital. The number of samples was 65 respondents taken by accidental sampling with inclusion criteria did not have diabetic ulcers, heart or kidney disease and exclusion criteria were ABI values> 1.3. Conclusion: The lower of ABI values indicate a problem of foot sensory in T2DM patients.It is recommended for T2DM patients to routinely to assest of ABI and leg sensitivity and control glikemic levels.